Muscle synergy analysis during badminton forehand overhead smash: integrating electromyography and musculoskeletal modeling - Tajik, R.; Dhahbi, W.; Fadaei, H.; Mimar, R. (Frontiers in Sports and Active Living, 2025)
Introduction: This study aimed to quantify shoulder muscle synergies during badminton forehand overhead smash (BFOS) via non-negative matrix factorization (NMF), validate musculoskeletal (MSK) models for high-speed movements by comparing electromyography (EMG)-derived synergies with simulation results, and explore the potential of NMF-based MSK models in advancing sports science.